2015
DOI: 10.1038/srep16118
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticles facilitate methane production from ethanol via acting as electron acceptors

Abstract: Potential for interspecies hydrogen transfer within paddy soil enrichments obtained via addition of magnetite nanoparticles and ethanol (named as PEM) was investigated. To do this, PEM derived from rice field of Hangzhou (named as PEM-HZ) was employed, because it offered the best methane production performance. Methane production and Fe (III) reduction proceeded in parallel in the presence of magnetite. Inhibition experiments with 2-bromoethane sulfonate (BES) or phosphate showed that interspecies hydrogen tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…28 It is noteworthy that the considerable enrichment of Thauera (60%) in the SEM was observed compared with the SEC (12.9%), indicating its important role in the conversion of propionate to methane. Thauera was also identied during the syntrophic oxidation of acetate and ethanol in paddy soil, 13,21 and has been described for its ability to reduce Fe(III) oxides using acetate and ethanol as electric donors under anaerobic conditions. 13,21,29 Thus, a high proportion of Thauera species identied in the SEM suggested that it was most closely related to reduction of Fe(III) in magnetite.…”
Section: Structure Of Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…28 It is noteworthy that the considerable enrichment of Thauera (60%) in the SEM was observed compared with the SEC (12.9%), indicating its important role in the conversion of propionate to methane. Thauera was also identied during the syntrophic oxidation of acetate and ethanol in paddy soil, 13,21 and has been described for its ability to reduce Fe(III) oxides using acetate and ethanol as electric donors under anaerobic conditions. 13,21,29 Thus, a high proportion of Thauera species identied in the SEM suggested that it was most closely related to reduction of Fe(III) in magnetite.…”
Section: Structure Of Microbial Communitiesmentioning
confidence: 99%
“…Thauera was also identied during the syntrophic oxidation of acetate and ethanol in paddy soil, 13,21 and has been described for its ability to reduce Fe(III) oxides using acetate and ethanol as electric donors under anaerobic conditions. 13,21,29 Thus, a high proportion of Thauera species identied in the SEM suggested that it was most closely related to reduction of Fe(III) in magnetite. Additionally, 16S rRNA-based Illumina sequencing of the archaeal community in the SEM revealed that Methanobacterium (11%) was the major dominant species, which utilizes H 2 and CO 2 to produce methane.…”
Section: Structure Of Microbial Communitiesmentioning
confidence: 99%
“…Many of these environments are rich in (semi)conductive minerals like magnetite (34,35), pyrite (36,37) or black carbon resulting from incomplete burning of plant biomass (38)(39)(40). Electrically conductive iron-oxide minerals and carbon chars (magnetite, granular activated carbon, biochar) were previously shown to stimulate direct interspecies electron transfer (DIET), a recently described form of interspecies electron transfer (12,(41)(42)(43)(44)(45)(46)(47)(48)(49), whereas strict H 2 -based interactions were shown to remain unaffected by the addition of conductive materials (44). DIET is a syntrophic association where electrons are transferred via conductive and/or redox active cell surface structures between an electron-donating species (electrogen) and an electron-accepting species (electrotroph) (47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%
“…Since sediment incubations are less defined than pure culture studies, other potential mechanisms could have been operative in addition to or instead of mDIET. Magnetite could have served as electron acceptor ( Yang et al, 2015 ), or as part of an iron redox cycle, could have been important in the production of H 2 from acetate to support hydrogenotrophic methanogenesis ( Jiang et al, 2013 ); however, iron reduction was not observed in our incubations concurrently while methanogenesis was on-going (Figure 1 ). More research is required to elucidate the exact mechanism for enhanced methanogenesis in the presence of crystalline iron oxides.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, Orenia might have been involved in iron reduction together with Pelobacter spp., who are capable of fermentative and dissimilatory Fe(III) reduction ( Lovley et al, 1995 ). Syntrophic interactions that occur between microbes and iron minerals during methanogenic fermentation of organic matter mediate the electron transfer during these interactions ( Kato et al, 2012 ; Yang et al, 2015 ). Although an isolated species within the genus, Orenia metallireducens strain Z6, can reduce both poorly crystalline and crystalline iron oxides ( Dong et al, 2016 ), the reduction of amended magnetite and hematite was not detectable based on a lack of increasing Fe 2+ concentrations at 30°C.…”
Section: Discussionmentioning
confidence: 99%